Investigasi Kualitas Air Pada Daerah Aliran Sungai Pisang Kota Padang-Sumatera Barat - Tanjung, Denny Akbar (Mahesa Research Center, 2023)
The aim of this research is to test water quality, including pH, conductivity, total dissolved solids (TDS), salinity, and turbidity. The research method uses quantitative methods. The research area includes 10 sample points around the Pisang river basin, Bungus Teluk Kabung, Padang, and West Sumatra. Samples were measured using a predetermined measuring instrument with three repetitions. Based on test results in all study areas, several water quality testing parameters met the standards of Ministry of Health Regulation No. 2 of 2023, such as pH and total solid density. Meanwhile, other parameters, such as salinity, conductivity, and turbidity, are still far from the predetermined thresholds. Treatment needs to be carried out so that the water can be used according to needs.